2005
DOI: 10.1002/jobm.200410504
|View full text |Cite
|
Sign up to set email alerts
|

Decolorization of diazo-dye Reactive Blue 172 byPseudomonas aeruginosa NBAR12

Abstract: A novel bacterial strain capable of decolorizing textile dyes was isolated from dye contaminated soil obtained from industrial estate of Ahmedabad, Gujarat, India. The bacterial isolate Pseudomonas aeruginosa NBAR12 was capable of decolorizing 12 different dyes tested with decolorization efficiency varying in the range of 80 to 95%. Maximum extent as well as rate of Reactive Blue 172 (RB 172) decolorization was observed when glucose (2 g x l(-1)) and yeast extract (2.5 g x l(-1)) were supplemented in the mediu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(40 citation statements)
references
References 33 publications
(29 reference statements)
0
38
1
1
Order By: Relevance
“…The effluent laden water of Noyyal at Tirupur as well as effluent at waste water treatment plants have bacteria like Pseudomonas sp. and Achromobacter sp., and these bacterial species have shown potential to decolorize the dye effluent color in different studies (Bhatt et al 2005;Blumel et al 2001). Also Bacillus sp.…”
Section: Aspergillus Nigermentioning
confidence: 99%
“…The effluent laden water of Noyyal at Tirupur as well as effluent at waste water treatment plants have bacteria like Pseudomonas sp. and Achromobacter sp., and these bacterial species have shown potential to decolorize the dye effluent color in different studies (Bhatt et al 2005;Blumel et al 2001). Also Bacillus sp.…”
Section: Aspergillus Nigermentioning
confidence: 99%
“…Bioremediation of azo dyes is a process that reduces and cleaves azo bond under anaerobic conditions. The formed aromatic intermediate further gets mineralized under aerobic conditions (Bhatt et al 2005;Tastan et al 2010). It has been suggested that the azo bond cleavage is catalyzed by azoreductase, which is very sensitive to oxygen in the medium (Nikolova and Nenov 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Fungal enzyme systems need low pH for optimal activity and longer retention times for complete decolorization (Swamy and Ramsay 1999). Bacteria studied for biodegradation include Pseudomonas NBAR (Bhatt et al 2005), Rhodopseudomonas palustris, etc. (Liu et al 2006).…”
Section: Introductionmentioning
confidence: 99%